Hegemonic Masculinity as Conventional Heroes in Pakistani Dramas: An Analysis - Khaleeli, Alizeh; Zafar Iqbal (Journal of Peace, Development and Communication, 2024)
Abstract: This research is a content analysis of four Pakistani dramas with conventional heroes and non-conventional heroes. In the Pakistani media landscape, the male protagonists are most often portrayed as “conventional heroes” upholding masculine hegemonic traits and norms. The male protagonists’ primary emotions depicted are rage and obsession. These conventional hero portrayals perpetuate limited visual representation. The portrayal of non-conventional heroes, resist the notions of masculine hegemony. Non-conventional heroes defy the characteristics of a conventional hero. Though non-conventional heroes in the Pakistani media landscape are few and far between, they have resonated with audiences. This paper examines the visual characterization of masculinity and analyses the construction of conventional and non-conventional heroes through narratives, visual framing and dialogues in Pakistani media.